Soviet era books for children and youth - Princeton University - Library (2022)
This digital collection represents imprints from the Russian holdings of the Cotsen Children’s Library. All of the selections in this group were produced between 1918 and 1938 and present examples of the visual and verbal idioms artists and authors used to address the country’s children and youth in the first two decades after the October Revolution.